Du robinet au consommateur : qualité de l’eau potable dans le contexte domestique de l’agglomération de Khartoum, Soudan - Emilie Lavie (Unité Mixte de Recherche 8504 Géographie-cités, 2014)
The city of Khartoum experienced a rapid growth and an urban spread towards its periphery that has become denser than the center. Urban planning was unable to follow the pace of demographic growth, and the establishment of a decent drinking water network is slow. The population is incited to be independent from quantitative variations by storing drinking water, because of water turbidity, many cuts, and pressure decreases. These bad habits of storage, the lack of efficiency of treatment and the absence of a collective supply network maintenance are responsible for a significant decrease in the physical and biological water quality. The result is a development of water-borne diseases (generally diarrheal symptoms and kidney diseases). This study demonstrates that the distinction made between quantity and quality in the institutional management of drinking water in Khartoum is a dead-end. It also suggests that treatment would be more efficient and water would have better quality if smaller quantity of drinking water were produced and the amount of wasted water were reduced.